The Formulation of Purple Sweet Potato Extract (Ipomoea batatas L.) Cream Blush as a Natural Colorant - Permatasari, Sabrina Destiani; Elisya, Yetri Elisya; Achmadi, Nanang Kurnia; Junaedi, Junaedi (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2025)
The use of synthetic dyes such as Red K.3 (CI 15585), Red K.10 (Rhodamine B), and Orange K.1 (CI 12075) is hazardous to health. Natural dyes can serve as an alternative to synthetic dyes, as they are significantly safer and more environmentally friendly. One plant that can be used as a natural dye is purple sweet potato (Ipomoea batatas L.). This study aims to identify the presence of anthocyanin compounds in purple sweet potato extract (Ipomoea batatas L.), evaluate the physical properties of blush on cream formulations based on this extract, and determine the most preferred concentration through a hedonic test. This study used an experimental technique. Purple sweet potatoes were extracted using the maceration method. The study involved preparing purple sweet potato extract-based blush on cream with varying extract concentrations of 8%, 9%, and 10%, as well as a negative control. Physical evaluation tests were conducted, including organoleptic testing, homogeneity testing, pH testing, and spreadability testing. A hedonic test was also performed. The test results showed that purple sweet potato extract contains anthocyanin compounds. The anthocyanin content indicates that purple sweet potato extract has the potential to be used as a natural dye. The cream blush formulations met all physical testing requirements. Based on the hedonic test, F2 (8%) and F3 (10%) cream blush were preferred by the panelists in terms of color, aroma, and texture.